Social capital among school children of Japanese-Filipino marriages - Jabar, Melvin A. (Animo Repository, 2013)
The paper aims to explore the formation and deployment of social capital in the education of children of Japanese-Filipino marriages in Oita Prefecture, Japan. It is based on 32 key informant interviews involving children, their parents, and their homeroom teachers. Social capital, in the form of parental involvement and the positive relationships of children with their teachers and classmates, was seen to help develop a positive environment for learning in both home and school environments